Shooting of Indonesian Migrants by Malaysian Authorities in the Perspective of International Human Rights Law - Aini, Hanifah Qurrotu; Triadi, Irwan (Siber International Journal of Advanced Law (SIJAL), 2025)
The incident of the shooting of five Indonesian migrant workers (PMI) by the Malaysian Maritime Enforcement Agency (APMM) in the waters of Tanjung Rhu, Selangor, on January 24, 2025, which resulted in two deaths and three injuries, highlights violations of human rights (HAM) and international legal norms.This research examines the actions of the Malaysian Maritime Enforcement Agency (APMM) that allegedly used excessive force and committed extrajudicial killings, violating Article 3 of the UDHR, Article 6 of the ICCPR, and Article 104 of Law No. 39/1999.The driving factors of illegal migration, such as the lack of job opportunities in Indonesia and the allure of high wages in Malaysia, are exacerbated by labor trafficking syndicates.The Indonesian government has sent diplomatic notes and provided legal assistance, but the weakness of bilateral agreements poses a challenge.This normative legal research recommends a systematic approach to law enforcement, eradication of labor trafficking, and protection of Indonesian Migrant Workers (PMI) to prevent the recurrence of tragedy.